PENGARUH PEMILIHAN MATERIAL TERHADAP KEKUATAN RANGKA MAIN LANDING GEAR UNTUK PESAWAT UAV: EFFECT OF MATERIAL SELECTION ON THE STRENGTH OF THE MAIN LANDING GEAR FRAME FOR UAV AIRCRAF - Lasinta Ari Nendra Wibawa (Program Studi Teknologi Informasi, 2019)
This study examined the effect of material selection on the strength of the main landing gear frame for UAV aircraft using the finite element method. Linear static analysis was carried out using Autodesk Inventor Professional 2017 software. Main landing gear frame using Aluminum 5052-H38, Aluminium 5083 87 Cold Formed, Aluminium 6061, and CFRP. UAV aircraft was weighing 85 kg with a landing speed of 10 m/s and impact time of 0,5 second. The simulation results show that the landing gear frames of the lightest in a row were CFRP, Al 5083 87 Cold Formed, Al 5052-H38, and Al 6061. Materials that have the greatest safety factor were CFRP, Al 5083 87 Cold Formed, Al 6061, and Al 5052-H38.